Family Knowledge about Hallucination Related to Drinking Medication Adherence on Schizophrenia Patient - Jek Amidos Pardede (Global Health Science Group, 2020)
Schizophrenia is a disease that affects the brain and causes strange and disturbing thoughts, perceptions, emotions, behavioral movements. Adherence is the level of patients carrying out treatment methods and behaviors suggested by the medicine or by others. This study aims to determine the relationship between family knowledge about schizophrenia and compliance with hallucination patients taking medication. The research design used was a descriptive correlation with a cross-sectional approach. The population in this study were all families who brought schizophrenic patients to the Polyclinic of Rumah Saki Jiwa Medan. The sample was 116 people and the sample was taken by purposive sampling. Data collection tools using a questionnaire that has been tested for validity and reliability. The results of this study were obtained, the majority of respondents' knowledge of schizophrenia was good as many as 69 people (59.5%), the level of compliance of patients with hallucination patients was obedient to 72 people (62.1%) and the chi-square statistical test ¬ showed (p = 0.001 ; p <0.005). In conclusion, there is a significant relationship between family knowledge about schizophrenia and patient adherence to hallucination patient medication.